Relation Of Knowledge About Diabetes Mellitus With Motivation To Prevent Complications In Pematang Reba The Working Area Of Pekan Heran`s Public Health Center Of Indragiri Hulu Regency - Alice Rosy (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2020)
Different levels of knowledge of diabetics will cause different motivations in preventing complications in people with diabetes mellitus. Most sufferers are in the Public Health Center of Pekan Heran, which is 330 patients. The purpose of this study was to determine the relationship of knowledge about Diabetes Mellitus with motivation in preventing complications in the Kelurahan Pematang Reba, Public Health Center Pekan Heran, Indragiri Hulu District. The research method is descriptive correlative with cross sectional approach, the sampling technique is total sampling, 70 respondents, by distributing questionnaires. Analysis of the data in this study is univariate and bivariate analysis. The results showed that the majority of sufferers' knowledge about diabetes mellitus was good (90%), most patients had strong motivation in preventing complications of diabetes mellitus (94.3%). There is a relationship between knowledge about Diabetes Mellitus with motivation in preventing complications with a p value of 0.02 or <0.05